PERENCANAAN PEMBANGUNAN PARTISIPATIF DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA(RPJMDES) DI DESA PANGKALAN BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR - Maripah "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Village development planning is an initial step taken by the village head along with the authorities in the village development process to manage the resources so that the village community can enjoy. An interesting phenomenon in the participatory development planning process also took place in Pangkalan Baru Village, Siak Hulu District, Kampar District, especially on the aspect of community participation in the preparation of the Village Medium Term Development Plan (RPJMDes). Planning comes from the word plan, which means the design or order of things to be done. From this simple understanding can be decomposed some important components, namely goals (what to achieve), activities (actions to realize the goal), and time (when, when the activity is about to do). This research uses qualitative research methods with descriptive data assessment. In data collection, researchers used interview techniques, observation and study literature. By using key informant and informant afterwards as source of information. The results of this study indicate that several stages of the development planning process in each village has not been implemented. At Sub-district Musrenbang level several stages of the development planning process have not been implemented, especially at the stage where the community has not been involved decide the priority of activities to be submitted to the district development planning process. And community participation in development planning in Siak Hulu District Kampar Regency is still low.Keywords: Participatory Development Planning